2021
DOI: 10.4102/sajhivmed.v22i1.1193
|View full text |Cite
|
Sign up to set email alerts
|

Ocular manifestations of people living with HIV in Tunisia

Abstract: Background: Ocular involvement is a common complication of human immunodeficiency virus (HIV). Knowledge about this topic in Tunisia is limited.Objective: To investigate ophthalmic manifestations in patients living with HIV in Tunisia.Method: This was an observational study, performed between January 2007 and December 2016. We included patients with ocular disorders related to HIV. The data were recorded retrospectively from chart review.Results: Amongst 98 people living with HIV (PLWH), 36 participants (55 ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
6
1
Order By: Relevance
“…Unlike reports in other studies, opportunistic ocular infections were rarely reported in our study [27]. This is expected because, as previously reported, many of the patients in this study were virologically suppressed, and their ocular abnormalities may be explained by a combination of factors, including the toxicity of antiretroviral therapy and the drugs used to treat OIs [28].…”
Section: Discussionsupporting
confidence: 53%
“…Unlike reports in other studies, opportunistic ocular infections were rarely reported in our study [27]. This is expected because, as previously reported, many of the patients in this study were virologically suppressed, and their ocular abnormalities may be explained by a combination of factors, including the toxicity of antiretroviral therapy and the drugs used to treat OIs [28].…”
Section: Discussionsupporting
confidence: 53%
“…Actually, the involvement of the anterior segment is more common than that of the posterior segment in the post-ART era. According to a study from Tunisia, dry eye (8%) is the most common manifestation in the anterior segment [ 14 ]. The prevalence of uveitis in patients with HIV is 1.1–24% [ 4 , 7 , 14 ].…”
Section: Prevalence Of Hiv and Its Related Ocular Compilationsmentioning
confidence: 99%
“…According to a study from Tunisia, dry eye (8%) is the most common manifestation in the anterior segment [ 14 ]. The prevalence of uveitis in patients with HIV is 1.1–24% [ 4 , 7 , 14 ]. However, considering that two-thirds of PLWH live in HIV high-burden countries [ 3 ], where the awareness of uveitis still needs to be improved, it is still an emergency for ophthalmologists to have more access to patients with HIV-related uveitis.…”
Section: Prevalence Of Hiv and Its Related Ocular Compilationsmentioning
confidence: 99%
“…Herpes Simplex is usually diagnosed clinically and requires no laboratory confirmation. If the diagnosis is in doubt, the following tests may assist: [5,9,21] 1.…”
Section: Diagnostic Proceduresmentioning
confidence: 99%
“…Herpes Simplex Keratitis was found in 5% of those patients. The risk of developing ocular disease in PLWH is higher when the CD4+ count is <200 cells/µL [21].…”
Section: Systemic Diseases-immunodeficiency Conditionsmentioning
confidence: 99%